La « femme·eux·ze » musique québécoise : La recherche sur les genres, les sexualités et autres pratiques non dominantes en musique au Québec (1874-2022) - Blais-Tremblay, Vanessa (Nouveaux cahiers de recherche, 2023)
C’est là un ouvrage de référence qui présente la recherche sur la musique, les genres et les sexualités, et plus largement la vie musicale non dominante au Québec depuis le dernier quart du XIXe siècle jusqu’à aujourd’hui. Issu des travaux réalisés en 202-2022 par le pôle universitaire DIG! Différences et inégalités de genre dans la musique au Québec (D!G), un réseau interdisciplinaire et intersectoriel qui réunit les chercheur·ses, publics, artistes et autres professionnel·les de la musique qui s’intéressent à cette thématique, l’ouvrage comprend une revue de la littérature et une bibliographie de plus de 800 ressources scientifiques.

Situer les femmes dans l'Electronic dance music culture (EDMC) à Montréal, entre 1950 et 1955 : premier survol - Van Vliet, Kiersten (Les Cahiers de la Société québécoise de recherche en musique, 2021)

Serving Each Other: Sharing Economies and Affective Labour in Montréal's Kiki Scene - Tailor, Jesse (Université Carleton, 2019)
Against a tense socio-political backdrop of white supremacy, intensifying pressures of neoliberal fiscal austerity, and queer necropolitics, this thesis addresses performance-based activist forms of place-making for urban-based queer, trans, and gender nonconforming communities of colour. Using participant observation and qualitative interviews with pioneering members of Montréal’s Kiki scene and Ottawa’s emerging Waacking community and interpreting my findings through the theoretical lens of queer of colour theory, critical whiteness studies, queer Latinx performance studies and Chicana feminism, I argue that Kiki subculture, which is maintained by pedagogical processes of ‘each one, teach one’, is instrumental in facilitating i) life-affirming queer kinship bonds, (ii) alternative ways to simultaneously embody and celebrate nonnormative gender expression with Black, Asian, and Latinx identity, iii) non-capitalist economies of sharing, and iv) hopeful strategies of everyday community activism and resilience to appropriative processes during economic insecurity and necropolitical turmoil.

La scène travestie qui est à l’origine du punk à Montréal - Desfossés, Félix B. (Vice, 2017)

DJ Mini and Montreal’s Vulgar Dance Music - Madden, David (Dancecult, 2016)
This article advances claims about Montreal’s electronic dance music scene through mapping the career of one of the key actors who shaped the electroclash scene from the early 2000s onwards—music producer/DJ Mini (née Evelyne Drouin). By way of detailing the career of DJ Mini, this text attempts to add to the queer musical narratives currently emerging from music scene analyses. Counter to the experiences of many women DJs and musicians participating in heterosexual and male-dominated music scenes, Drouin received extensive mentoring and support from various informal queer social networks spread throughout the circuits of the city. Not only did she gain access to a local production network of equipment and skill sharing, Drouin was also given access to spaces where she was able to develop production skills on her own time and at her own pace. DJ Mini’s story offers a telling case for the ways in which the politics of access—institutional, social, technological—remain central to the vitality and inclusivity of local music scenes.